Smoke promotes germination of peatland bryophyte spores. (18th October 2022) - Yusup, Shuayib; Sundberg, Sebastian; Ooi, Mark K J; Zhang, Mingming; Sun, Zhongqiu; Rydin, Håkan; Wang, Meng; Feng, Lu; Chen, Xu; Bu, Zhao-Jun
Abstract: Northern peatlands are globally important carbon stores. With increasing fire frequency, the re-establishment of bryophytes becomes crucial for their carbon sequestration. Smoke-responsive germination is a common trait of seeds in fire-prone ecosystems but has not been demonstrated in bryophytes. To investigate the potential role of smoke in post-fire peatland recovery, we tested the germination of spores of 15 bryophyte species after treatment with smoke-water. The smoke responsiveness of spores with different laboratory storage times and burial depths/age (3–200 years) was subsequently tested. Smoke increased the germination percentage for 10 of the species and the germination speed for four of these. Smoke responsiveness increased along the fire frequency gradient from open expanse to forest margin, consistent with the theory that this selects for the maintenance of fire-adapted traits. Smoke enhanced the germinability of 1-year but not 4-year laboratory-stored spores, and considerably increased the germinability of spores naturally buried in peat for up to ~ 200 years. The effect of fire may be overlooked in non-fire-prone ecosystems, such as those in which wetland bryophytes dominate. Our study reveals a mechanism by which an increase in fire frequency may lead to shifts in species dominance, which may affect long-term carbon sequestration in peatlands. Abstract : Smoke increased the spore germination percentage in 10 of 15 bryophyte species, and smoke responsiveness increased along the fire frequency gradient. Bryophyte spores buried naturally in peat for ~200 years showed enhanced germinability in response to smoke.